2014
DOI: 10.1038/srep07456
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 protects against apoptosis by promoting autophagy in degenerative human disc nucleus pulposus cells

Abstract: SIRT1 could protect degenerative human NP cells against apoptosis, and there were extensive and intimate connection between apoptosis and autophagy. Up to now, the role of autophagy in the process of human IVD degeneration is unclear. We sought to explore the relationship between autophagy and human IVD degeneration and to understand whether autophagy is involved in the protective effect of SIRT1 against apoptosis in NP cells. Our results showed that the autophagosomes number, the mRNA level of LC3 and Beclin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 50 publications
4
103
0
Order By: Relevance
“…76,77 An altered level of autophagy during intervertebral disc degeneration and aging has been reported. [37][38][39][40]78 Our studies clearly show evidence of MTOR-independent, noncanonical autophagy in NP cells. In addition, hypoxic induction of autophagy is independent of HIF1 as well as increased oxidative stress.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…76,77 An altered level of autophagy during intervertebral disc degeneration and aging has been reported. [37][38][39][40]78 Our studies clearly show evidence of MTOR-independent, noncanonical autophagy in NP cells. In addition, hypoxic induction of autophagy is independent of HIF1 as well as increased oxidative stress.…”
Section: Discussionmentioning
confidence: 66%
“…Although the causative relationship between disc degeneration and autophagy is not yet clear, alterations in the level of autophagy have been observed in degenerated IVDs, IVDs of aged or diabetic rats [37][38][39] and NP cells derived from degenerative human discs. 40 In addition, various stresses such as high glucose, 41,42 aberrant mechanical compression, 43 lactate overload, 44 glucosamine, 45 and reactive oxygen species (ROS), 43 activate autophagy in NP cells, further implicating autophagy modulation as a possible contributor to disc pathologies. However, studies investigating the mechanisms of how basal autophagy is controlled in NP cells and the role of physiological stimuli in this process are mostly lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although a causal relationship between autophagy defects and IDD has not yet been established, our findings showed that FOXO function promotes NP cell survival under oxidative and inflammatory stresses, major drivers of NP cell apoptosis and aging‐related IDD (Nasto et al, 2013; Wang et al, 2013; Yang et al, 2014), and thus suggest that activation of FOXO in aged IVD could increase autophagy and protect NP cells from stress‐induced apoptosis. Further supporting this hypothesis, various studies have shown that autophagy activation can protect NP cells against different apoptotic insults (Jiang, Jin, Wang, Jiang, & Dong, 2014; Jiang, Zhang, et al, 2014). …”
Section: Discussionmentioning
confidence: 72%
“…The protein extracts were then electrophoretically resolved by SDS-PAGE (10-20 mg protein/lane) and transferred onto PVDF membranes for immunoblot analysis. The blots were processed (19)(20)(21) and then probed with the indicated antibodies. The after antibodies were used for b-actin (47778; Santa Cruz Biotechnology, TX, USA), a2tubulin (T5168; Sigma-Aldrich), SIRT1 (07-131; EMD-Millipore), Ac-H3K9/14 (A-4021-050; EMDMillipore), 2MeH3K9 (07441; EMD-Millipore), MMP13 (sc-81547; Santa Cruz Biotechnology), LEF1 (2230; Cell Signaling Technology ), and b-catenin (ab16051; Abcam, Cambridge, United Kingdom).…”
Section: Protein and Immunoblot Analysesmentioning
confidence: 99%
“…Correspondingly, additional in vivo studies (14) demonstrated that Sirt1 exerts an anti-inflammatory effect in cartilage during OA. Moreover, mechanistic studies have provided further support that SIRT1 promotes chondrocyte survival through various pathways (15)(16)(17)(18)(19)-in particular, deacetylation of p65/ RelA-which reduces iNOS gene expression after IL-1b challenge of chondrocytes (20). Despite the wealth of information regarding the beneficial effects exerted by SIRT1 in maintaining chondrocyte survival and attenuating inflammation, very little is known about the impact of SIRT1 on cartilage destruction during OA.…”
mentioning
confidence: 99%